2014
DOI: 10.1002/jor.22743
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of synovial fluid in a unilateral ovine model of anterior cruciate ligament reconstruction of the knee suggests biomarkers for early osteoarthritis

Abstract: Joint injuries and subsequent osteoarthritis (OA) are the leading causes of chronic joint disease. In this work, we explore the possibility of applying magnetic resonance spectroscopy-based metabolomics to detect host responses to an anterior cruciate ligament (ACL) reconstruction injury in synovial fluid in an ovine model. Using multivariate statistical analysis, we were able to distinguish post-injury joint samples (ACL and sham surgery) from the uninjured control samples, and as well the ACL surgical sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…A decrease in the methionine concentration indicates its utilization, where it is likely converted to S‐adenosylmethionine (SAM), which has been proposed as a cartilage damage repairing and inflammatory reducing factor . Interestingly, the metabolic pathways and physiological conditions highlighted here (i.e., hypoxia, inflammation and high energy requirements) are similar to those described in previous metabolomics studies of OA in SF . However, specific differences between metabolites could be due to the fact that some of the earlier studies focused on OA in animal models only or were lacking a healthy control group when examining a human population .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A decrease in the methionine concentration indicates its utilization, where it is likely converted to S‐adenosylmethionine (SAM), which has been proposed as a cartilage damage repairing and inflammatory reducing factor . Interestingly, the metabolic pathways and physiological conditions highlighted here (i.e., hypoxia, inflammation and high energy requirements) are similar to those described in previous metabolomics studies of OA in SF . However, specific differences between metabolites could be due to the fact that some of the earlier studies focused on OA in animal models only or were lacking a healthy control group when examining a human population .…”
Section: Discussionmentioning
confidence: 55%
“…As a follow‐up to our recent study of synovial fluid in a sheep model of early OA, in the current contribution we have used proton nuclear magnetic resonance ( 1 H NMR) spectroscopy and gas chromatography‐mass spectrometry (GC‐MS) to identify metabolic patterns in SF of symptomatic chronic knee OA patients. An advantage of NMR is that this technique is quantitative, highly reproducible and can be executed in high‐throughput large subclinical settings .…”
mentioning
confidence: 99%
“…The study, demonstrated the potential of this approach to help create a more systematic metabolome analysis16. Other recent studies in farm animals confirm the potential of NMR technique to metabolomics approaches17181920.…”
mentioning
confidence: 54%
“…In the category of animal products, bovine-based studies had the most articles published (16 articles) relative to all other groups. Some of the more interesting applications of metabolomics found in our survey include the use of metabolomics for quality control of animal products [46; 47], evaluating nutritional value and impact of various feed sources on animal health and products [25], investigating disease biology by using animal models of human disease [48; 49], investigation of potential metabolite biomarkers of animal disease [22; 23], assessment of production traits [50; 51], reproductive performance [29], and general metabolome characterization [52; 53]. …”
Section: Resultsmentioning
confidence: 99%